Katowice Region in the Light of the Selected Conceptions of Social-Economic Transformations - Runge, Jerzy (Bulletin of Geography. Socio-economic Series, 2009)
Taking into consideration all conceptions of economic and social development discussed here it should be concluded that -- non of the classical models of social transformation is represented in the Katowice region in homogeneous form. In fact, only modernisation (as it is a historical aspect) is most distinguished among others; -- it is possible that features typical for several models of economic or social transformations occur at the same time. This concerns spatial approaches. The consequence of frequent fragmentation of social-economic reality in numerous theoretical conceptions and proposals of restructuring changes is a narrow understanding of the research problems. It seems, therefore, that conceptions of social development created on the basis of sociology may be successfully applied in social geography. The condition here is not only taking into account spatial aspects but also the possibility of applying several models of transformations at the same time.